An SMA Passive Ankle Foot Orthosis: Design, Modeling, and Experimental Evaluation. (2nd June 2014) - Deberg, Liberty; Taheri Andani, Masood; Hosseinipour, Milad; Elahinia, Mohammad
Abstract : Shape memory alloys (SMAs) provide compact and effective actuation for a variety of mechanical systems. In this work, the distinguished superelastic behavior of these materials is utilized to develop a passive ankle foot orthosis to address the drop foot disability. Design, modeling, and experimental evaluation of an SMA orthosis employed in an ankle foot orthosis (AFO) are presented in this paper. To evaluate the improvements achieved with this new device, a prototype is fabricated and motion analysis is performed on a drop foot patient. Results are presented to demonstrate the performance of the proposed orthosis.